Pandemic stressors and depressive symptoms: Examining within- and between-person effects of neuroticism. (November 2022) - Morstead, Talia; Zheng, Jason; Sin, Nancy L.; Rights, Jason D.; DeLongis, Anita
Abstract: Experiencing stressors related to the COVID-19 pandemic such as health-related concern, social isolation, occupational disruption, financial insecurity, and resource scarcity can adversely impact mental health; however, the extent of the impact varies greatly between individuals. In this study, we examined the role of neuroticism as an individual-level risk factor that exacerbates the association between pandemic stressors and depressive symptoms. With repeated assessments of pandemic stressors and depressive symptoms collected from 3181 participants over the course of the pandemic, we used multilevel modeling to test if neuroticism moderated the association between pandemic stressors and depressive symptoms at both between- and within-person levels. At the between-person level, we found that participants who reported more pandemic stressors on average had higher levels of depressive symptoms and that this association was stronger among those high in neuroticism. At the within-person level, reporting more pandemic stressors relative to one's average on any given occasion was also associated with heightened depressive symptoms and this effect was similarly exacerbated by neuroticism. The findings point to pandemic stressor exposure and neuroticism as risk factors for depressive symptoms and, in demonstrating their synergistic impact, may help identify individuals at greatest risk for adverse psychological responses to the COVID-19 pandemic. Highlights: Examines the association between COVID-19 stressors and depressive symptoms. Those reporting more stressors tended to report more depressive symptoms across time. During periods when stressors increased, depressive symptoms also tended to increase. Those higher in neuroticism had greater reactivity to stressor exposure. Findings point to COVID-19 stressors and neuroticism as risk factors for depression.